2016
DOI: 10.1016/j.cvex.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and Disorders of the Oral Cavity of Rat-like and Squirrel-like Rodents

Abstract: The order Rodentia comprises more than 2000 species divided into 3 groups based on anatomic and functional differences of the masseter muscle. Myomorph and sciuromorph species have elodont incisors and anelodont cheek teeth, unlike hystrichomorph species which have full anelodont dentition. Diseases of incisors and cheek teeth of rat-like and squirrel-like rodents result in a wide variety of symptoms and clinical signs. Appropriate diagnostic testing and imaging techniques are required to obtain a definitive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
(125 reference statements)
4
11
0
Order By: Relevance
“…Pseudo-odontoma was considered appropriate for some of the dysplastic changes, particularly the abnormal matrigenesis, observed at the molar apices but not for the masses of markedly disrupted, haphazardly organized and proliferative odontogenic epithelium. Despite these challenges, the gross and histopathologic features here are very similar to those described in rat-like and squirrel-like rodents, 1,2,13,22 rabbits, 17 and other voles 29 though less proliferative and destructive than those described in guinea pigs and degus. 2,4,16,19,23 Observations in CSF-1-deficient, 14 Snx10-deficient and bisphosphonate-treated (personal observations, D. Imai) osteopetrotic rodents have confirmed that microtraumatic disruption and fragmentation of odontogenic epithelium by bone can produce isolated and disorganized islands of proliferative odontogenic epithelium that can subsequently proliferate into odontoma-like masses.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Pseudo-odontoma was considered appropriate for some of the dysplastic changes, particularly the abnormal matrigenesis, observed at the molar apices but not for the masses of markedly disrupted, haphazardly organized and proliferative odontogenic epithelium. Despite these challenges, the gross and histopathologic features here are very similar to those described in rat-like and squirrel-like rodents, 1,2,13,22 rabbits, 17 and other voles 29 though less proliferative and destructive than those described in guinea pigs and degus. 2,4,16,19,23 Observations in CSF-1-deficient, 14 Snx10-deficient and bisphosphonate-treated (personal observations, D. Imai) osteopetrotic rodents have confirmed that microtraumatic disruption and fragmentation of odontogenic epithelium by bone can produce isolated and disorganized islands of proliferative odontogenic epithelium that can subsequently proliferate into odontoma-like masses.…”
Section: Discussionsupporting
confidence: 71%
“…In the absence of direct occlusal contact and vertical pressure, coronal eruption may not be inhibited as quickly and apical elongation may be delayed. This difference in occlusal apposition and masticatory force between molar and incisor teeth and the absence of any repetitive incisor trauma 1,2,22 could explain why apical elongation (with one exception in the California vole collection) was not observed in the incisors of the Amargosa voles. Histopathologic incisor apical abnormalities may still be present in the Amargosa voles, but were not evaluated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The inherent incisor tooth structural variations between the root and crown due to the larger part of the dental root pulp and higher dentine crown mass, as well as dentine-enamel ratio, could be the key factors in the accumulation of Pb-T differences [ 33 ]. The rodent incisors are predominantly dentine with a thin layer of enamel located only in the front part of the tooth [ 30 ]. The influence of the presence of the large dentine mass in the crown of incisor teeth may have been one of the contributing factors behind the L2 or U2 in the low Pb group accumulating much Pb than the L1 or U1 in the high Pb exposure group.…”
Section: Discussionmentioning
confidence: 99%
“…However, the present findings agreed in part with a report in human incisor teeth samples where most of the Pb were primarily deposited in the secondary dentine region close to the pulp, and secondarily, at surface enamel [ 12 ]. Moreover, the observed high intensities of Pb in the outer part of incisors were only on the front side, the only side bearing enamel in rodent incisors [ 30 ]. This phenomenon has been demonstrated in both erupted and non-erupted teeth that highly accumulated Pb in the outer enamel surface and with a gradual reduction of Pb in the deeper layers of the enamel [ 19 , 39 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation